2016
DOI: 10.1111/cfs.12310
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing the virtuous circle: Looked After Children's participation in reviews, a cyclical and relational process

Abstract: Children's participation in decision making of all kinds is of increasing interest across the world as more and more countries seek to comply with Article 12 of the United Nations Convention on the Rights of the Child. The participation rights of children who are in the care of the state are of particular concern. Recent research in England suggests that Independent Reviewing Officers (IROs) can play a crucial role in ensuring that looked after and accommodated children are able to participate in care planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In one study, workers reported that children’s participation affected the outcome of decision making in half of the cases (Vis & Thomas, 2009). In another study, Roesch-Marsh et al (2017) found that over 50% of the workers surveyed felt that the young person’s participation had a good deal of impact on the decisions made in the meeting and 10% felt that the young person’s participation determined the decisions made in the review. Oppenheim-Weller et al (2017) reported a low agreement among participants that children’s opinions influenced the decisions.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, workers reported that children’s participation affected the outcome of decision making in half of the cases (Vis & Thomas, 2009). In another study, Roesch-Marsh et al (2017) found that over 50% of the workers surveyed felt that the young person’s participation had a good deal of impact on the decisions made in the meeting and 10% felt that the young person’s participation determined the decisions made in the review. Oppenheim-Weller et al (2017) reported a low agreement among participants that children’s opinions influenced the decisions.…”
Section: Resultsmentioning
confidence: 99%
“…You get to choose whoever’s there, like anyone you want to make you obviously feel like, more at ease because it’s your review.The option to bring a friend or close family member to such an important meeting seems likely to be particularly pertinent for a young person who lacks an established relationship with professionals. Likewise, since feeling comfortable and relaxed often stems from feeling in control, it is not surprising that those young people who chaired their own reviews, as well as those who set the agenda for the meeting, expressed more positive views about the review process (Roesch-Marsh, Gillies and Green, 2016; Thomas and O’Kane, 1999). Indeed, Thomas and O’Kane have developed tools for young people to use in deciding what items should be on the agenda (Thomas, et al., 1999).…”
Section: Resultsmentioning
confidence: 99%
“…According to the UN, child participation involves ‘…ongoing processes, which include information‐sharing and dialogue between children and adults based on mutual respect, and in which children can learn how their views and those of adults are taken into account and shape the outcome of such processes’ (UN Committee on the Rights of the Child, 2009, p. 5). It is understood as a process in which children have influence on decision‐making (Ballesté & Moudelle, 2016; Cahill & Dadvand, 2018; Collins, 2017; Damiani‐Taraba et al., 2018; Gallego‐Henao, 2015; Roesch‐Marsh et al., 2017; Sæbjørnsen & Willumsen, 2017). Fundamentally, participation should be taken seriously, and empower children in decisions about their own lives, their family and their communities (KII academic, May; KII academic, June; KII consultant, June; KII NGO Advocate, July; KII researcher advocate, June).…”
Section: Conceptualisationsmentioning
confidence: 99%
“…Caputo, 2017; Seim & Slettebø, 2017) and must account for socio‐cultural (Cahill & Dadvand, 2018; Fylkesnes et al, 2018; Theis, 2007), political (Barilá & Amoroso, 2017) and economic contexts (Theis, 2007). The process generally involves preparation, review and action (Roesch‐Marsh et al., 2017); reciprocal sharing of information, respect and dialogue, and feedback to children (van Bijleveld et al, 2015; Tisdall, 2017). Bordenave (1994), a Paraguayan academic, defined participation as a collective experience learned through group praxis, whereby participation is learned while participating.…”
Section: Conceptualisationsmentioning
confidence: 99%